2006
DOI: 10.2355/isijinternational.46.407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Slag Composition on Slag–Iron Interfacial Tension

Abstract: Interfacial tensions between liquid iron and slag were examined for CaO-SiO 2 binary and CaO-SiO 2 -Al 2 O 3 ternary slag systems. The influences of FeO, MgO, B 2 O 3 , TiO 2 , BaO and ZrO 2 in slag on the interfacial tension were also investigated by varying these oxides from 1-30 wt% in the CaO-SiO 2 binary or CaO-SiO 2 -Al 2 O 3 ternary slag systems.The interfacial tensions were determined by the sessile drop technique under argon atmosphere at 1 853 K. An X-Ray radiographic technique was employed to image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 7 publications
5
33
0
Order By: Relevance
“…This effect of free oxygen ions on the slag surface is also supported by the interfacial tension data of Bretonnet et al [24] in the CaO-Al 2 O 3 binary slag system and Sun et al [25] in the CaO-SiO 2 -Al 2 O 3 ternary slag system shown in Figs. 13 and 14, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…This effect of free oxygen ions on the slag surface is also supported by the interfacial tension data of Bretonnet et al [24] in the CaO-Al 2 O 3 binary slag system and Sun et al [25] in the CaO-SiO 2 -Al 2 O 3 ternary slag system shown in Figs. 13 and 14, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…According to literature [17,18], γ LO,LM is of the order of 1 N/m. Furthermore, the interfaces should at least contain five grid points for a sufficient resolution of the diffuse transition at interfaces and to reproduce accurately the surface energies [19].…”
Section: Constant Parametersmentioning
confidence: 99%
“…The formation of solid phases in slag increases the viscosity at process temperature, which leads to slow down the transfer of reactants and products near the slag/metal interface [14][15]. On the other hand, some researchers assume that the formation of solid spinel phases decrease the slag/metal interfacial tension, which results finally an increase in interfacial reaction kinetics [8,21]. The several SEM images from slag samples confirm the presence of spinel phases, the bright large angular particles, which are marked by circles on Figure 5(b).…”
Section: Resultsmentioning
confidence: 99%
“…The melting time was approximately 90 minutes. After the Armco-iron has been melted down under Ar gas atmosphere at 600 mbar, the electrolytic manganese (17)(18)(19)(20)(21)(22) wt.-%) was added to the melt. The chemical composition of Armco-iron and electrolytic manganese are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation